Demography and the dual epidemics of tuberculosis and HIV: Analysis of cross-sectional data from Sub-Saharan Africa. - Gambo Aliyu; Samer S El-Kamary; Alash'le Abimiku; William Blattner; Manhattan Charurat (PLoS ONE, 2018)
BACKGROUND:Convergence of tuberculosis (TB) and HIV epidemics is associated with higher morbidity and mortality risks and understanding their distribution across key demographic factors is essential for prevention and control. This analysis examines the prevalence of TB, HIV and TB-HIV coinfection across age and gender in patients with presumptive TB seeking care at the National TB and Leprosy Training Center in Nigeria. METHODS:Samples from 1603 presumptive pulmonary TB cases who provided informed consent were evaluated with a sequential testing algorithm that included a smear microscopy, cultures in liquid and broth media and then genotyping by Hain line probe assays. HIV was serially tested with two HIV rapid assays and retested with a third assay in non-conclusive samples. RESULTS:Twenty-three percent (375/1603) had confirmed pulmonary TB infection, 23.6% (378/1603) were positive for HIV infection and 26.9% (101/375) of the confirmed TB cases were HIV co-infected. Males had a higher prevalence of TB: 27.6% vs. 18.0%, p < .0001; and a lower prevalence of HIV: 19.0% vs. 29.6%, p < .0001. In the age range of 25-29 years, males were twice as likely to have TB (OR = 2.2; 95% confidence interval [CI]: 1.3-3.9, p = 0.0032) while females were five times more likely to have HIV (OR = 4.8; 95% CI: 2.6-8.9, p < .0001). Persons with TB-HIV coinfection were more likely to be young, female and less likely to be married. CONCLUSION:Younger females with a high burden of HIV may be under-diagnosed and under-reported for TB in Nigeria. Community programs for intensified and early detection of TB and HIV targeting younger females are needed in this setting.